A 30-year (1988-2017) study of Mute Swans Cygnus olor in Riga, Latvia - Matrozis, Ruslans (Wildfowl, 2019)
Ringing of Mute Swans Cygnus olor in Riga and its surrounding area (c. 500 km2) has been undertaken since January 1988. Numbers breeding in this area currently amount to c. 40 pairs, with c. 150–200 swans wintering in the region. A total of 2,446 individuals were ringed over a 30-year period (1988–2017), and 42,968 sightings or recoveries of these birds were recorded, with an average of 16 sightings per swan (up to 544 sightings for one individual). During the study, 295 (12.1%) individuals were seen abroad, with the longest migration distances being to the Netherlands (1,267 km) and the Ukraine (1,238 km) in severe winters. Sightings of 144 swans ringed in other countries were also recorded in Riga, mostly (54.2%) from Lithuania. The mean date on which migrating swans were first identified in Riga each spring was 11 March (range: 26 February–4 April during 2004–2017). Two spring migration waves were detected: the first was a continuous period of 3–4 weeks from the initial arrival day, while the second, at the end of May and beginning of June, was of non-breeding swans migrating to their moulting sites. First successful breeding was observed during the 3rd and 4th calendar years of life, but most swans (68%) started breeding between the ages of 4–6 years. Longest runs of successive successful breeding seasons (i.e. without skipping a year) were 10 years (male) and 11 years (female). Oldest successful breeders were 15+ years (for a male first ringed as an adult) and 16+ years (female), whilst the maximum number of cygnets produced during the life-time of one swan was 46 (for a male) and 59 (for a female). Hatching locations were known for 197 swans and five subsequently found breeding were all < 10 km from their natal territory, indicating that natal dispersal typically occurred over short distances. Of the 2,446 ringed swans, 620 were found dead or re-sighted in at least two winter periods, of which most (87%) were sighted in at least 5 winters, up to a maximum of 16 winter seasons. Only 4.5% were sighted or recovered > 10 years after ringing; the maximum age recorded was 17 years (male) and 18+ years (female). Polish morph Mute Swans were rarely observed in Riga; only 14 such individuals were ringed in total (0–3 per year between 2004 and 2017), representing 0.57% of all swans ringed during the study.